A Practical Guide to the Management of Subacute Stent Thrombosis - Vinall, Maria (MD Conference Express, 2011)
This article discusses a stepwise practical guide to managing stent thrombosis, which is multifactorial, involving issues that are related to the patient, lesion, device, procedure, platelet and coagulation factors, and stent-artery interactions.